PENGEMBANGAN PROGRAM PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA CALON GURU FISIKA DALAM MENYUSUN PROGRAM PEMBELAJARAN YANG MENGINTEGRASIKAN NILAI AGAMA ISLAM - Rochman, Chaerul (2010)
A prospective physics teacher graduating from an Islamic Higher Education Institution (PTAI) has to possess content and subject matter knowledge of physics learning and an ability to integrate Islamic values into instructional processes. This research aims at describing the Islamic values, the importance of integrating them into physics learning, to develop of physics learning program, describing the relation of student' ability components, and the supplementary factors and constraints in integrating the Islamic values into physics learning program. It applies research and development method, consisting of a preliminary study, model construction, model improvement, and verification phase of physic learning program based on Islamic values. The other parts of this research adopt a descriptive method. Data were collected by using the following instruments, test, portfolio, quetionnaire and interview. Based on the data analysis, the finding shows that: (1) Islamic values and the importance of integrating Islamic values are based on values Iman, Islam and Ihsan. Those Islamic values are described in physics learning program by integrating seven principal values such as honesty, discipline, fairness, cooperation, vision, responsibility, and care; (2) learning program made the change of student ability on planning of physics learning (N-gain 0,39); (3) the average student ability to integrate Islamic values into matter and physics lesson planning is 63 per cent; (4) the correlation between the students' academic to integrate Islamic values into their study is strong (r= 0,72); and (5) factors that support the implementation of integration of Islamic value into physics learning program are: vision, mission, and characteristic; curriculum structure, and program, student interest, relevant teaching material, pioneering team teaching; and the obstruct factors are lack of understanding and awareness of Islamic values integration, access of information to the vision and mission, and expert. Calon guru Fisika pada Perguruan Tinggi Agama Islam (PTAI) harus memiliki kemampuan utama dalam materi, pembelajaran fisika, dan diharapkan mampu mengintegrasikan nilai Agama Islam pada pembelajarannya. Penelitian ini bertujuan untuk mendeskripsikan nilai Agama Islam, urgensi integrasi nilai Agama Islam dalam pembelajaran Fisika, mengembangkan program pembelajaran Fisika, mendeskripsikan hubungan antar komponen kemampuan mahasiswa, serta mendeskripsikan faktor pendukung dan penghambat implementasi pengintegrasian nilai Agama Islam pada pembelajaran Fisika. Penelitian ini menggunakan metode research and development yang terdiri dari tahap pendahuluan, perancangan, pengembangan dan tahap verifikasi terhadap program pembelajaran Fisika berbasis nilai Agama Islam. Pada beberapa bagian lainnya dilakukan analisis deskriptif. Data-data penelitian diperoleh dengan menggunakan instrumen tes, portofolio, angket dan wawancara. Berdasarkan hasil penelitian, diperoleh: (1) nilai Agama Islam dan urgensi integrasi nilai Agama Islam didasarkan kepada nilai Iman, Islam dan Ihsan. Nilai-nilai tersebut dideskripsikan dan mendasari program pembelajaran Fisika dengan mengintegrasikan nilai jujur, disiplin, adil, kerjasama, visioner, tanggung jawab, dan peduli; (2) pengembangan program pembelajaran menyebabkan perubahan kemampuan mahasiswa dalam penguasaan perencanaan pembelajaran Fisika (N-gain 0,39); (3) prosentase kemampuan mahasiswa dalam mengintegrasikan nilai Agama Islam pada materi dan RPP Fisika berada pada 63,5%; (4) hubungan antara kemampuan akademik mahasiswa dalam mengintegrasikan nilai Agama Islam pada pembelajaran berkorelasi tinggi (r = 0,72); dan (5) terdapat beberapa faktor yang mendukung dan menghambat implementasi integrasi nilai Agama Islam pada pembelajaran Fisika